Ensuring Data Safety: Pharmacovigilance Processes, ADR Reporting, Regulatory Bodies, and Software Solutions - Akshitha Kandukuri; David Raj Edla (Asian Journal of Pharmaceutical Research and Development, 2025)
Pharmacovigilance (PV) is essential for ensuring drug safety by monitoring, detecting, assessing, and preventing adverse drug reactions (ADRs). Pharmacovigilance can be traced back to the thalidomide disaster in the 1960s, which resulted in the implementation of stringent drug safety regulations around the world. Signal detection, case processing, risk assessment, periodic reporting, and regulatory compliance are all part of the pharmacovigilance process, which aims at minimizing risks. Pharmacovigilance processes are monitored by a number of regulatory authorities around the world, including the FDA (Food and Drug Administration) in the United States, the EMA (European Medicines Agency), the MHRA (Medicines and Healthcare Products Regulatory Agency) in the United Kingdom, the CDSCO (Central Drugs Standard Control Organization) in India, and WHO’s Uppsala Monitoring Centre. These organizations ensure that pharmaceutical companies follow safety guidelines and report ADRs properly.ADRs are reported using standardized forms such as MedWatch (FDA), Yellow Card (UK), and suspected adverse drug reporting forms(India). The data is processed using pharmacovigilance software such as Argus Safety, ArisG, VigiFlow, Vigi base, and Oracle AERS, facilitating case management, signal detection, and regulatory submissions. Beyond drug safety, pharmacovigilance has developed into specialized domains such as materiovigilance, which monitors the safety of medical devices, and ecovigilance, which evaluates the environmental impact of pharmaceutical products. Both fields ensure medical advancements do not harm public health or ecosystems.